2010
DOI: 10.1302/0301-620x.92b7.23671
|View full text |Cite
|
Sign up to set email alerts
|

Total shoulder replacement for osteoarthritis in patients 80 years of age and older

Abstract: This study was performed to review the safety and outcome of total shoulder replacements in patients who are > or = 80 years of age. A total of 50 total shoulder replacements in 44 patients at a mean age of 82 years (80 to 89) were studied. Their health and shoulder status, the operation and post-operative course were analysed, including pain, movement, patient satisfaction, medical and surgical complications, radiographs, the need for revision surgery, and implant and patient survival. A total of 27 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 22 publications
(16 reference statements)
4
73
1
1
Order By: Relevance
“…16 We did not see a difference between men and women, which has been previously reported. 15,22 Other authors have also reported that the development of rotator cuff tears after surgery influences the development of RLLs, but this was not found in our series.…”
Section: Discussionsupporting
confidence: 64%
“…16 We did not see a difference between men and women, which has been previously reported. 15,22 Other authors have also reported that the development of rotator cuff tears after surgery influences the development of RLLs, but this was not found in our series.…”
Section: Discussionsupporting
confidence: 64%
“…Although the different types of shoulder arthroplasty usually are successful for treatment of a wide range of glenohumeral disorders [4,10,15,20,31,32,46,47,49,52], the results of these procedures are unpredictably variable: a substantial number of patients having shoulder arthroplasty experience minimal to no improvement or complications. Some of the factors previously associated with poorer results include patients with shoulders with multiple surgeries before the arthroplasty, patients with shoulders with work acquired injuries, patients with comorbidities, and surgeons with limited arthroplasty experience [3, 5, 7, 17, 21, 25, 27-29, 41, 54, 56, 57].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in shoulder function and pain as measured by the OSS was both statistically and clinically significant. Previous studies of shoulder arthroplasty in patients with RA and OA have similarly found improvement in function and pain (Norris and Iannotti 2002, Deshmukh et al 2005, Haines et al 2006, Sperling et al 2007, Raiss et al 2008, Foruria et al 2010, Ekelund and Nyberg 2011). …”
Section: Discussionmentioning
confidence: 76%